Algebraic solutions of flow and heat for some nanofluids over deformable and permeable surfaces. Issue 10 (2nd October 2017) - Turkyilmazoglu, Mustafa
Abstract : Purpose: This paper aims to working out exact solutions for the boundary layer flow of some nanofluids over porous stretching/shrinking surfaces with different configurations. To serve to this aim, five types of nanoparticles together with the water as base fluid are under consideration, namely, Ag, Cu, CuO, Al2 O3 and TiO2 . Design/methodology/approach: The physical flow is affected by the presence of velocity slip as well as temperature jump conditions. Findings: The knowledge on the influences of nanoparticle volume fraction on the practically significant parameters, such as the skin friction and the rate of heat transfer, for the above considered nanofluids, is easy to gain from the extracted explicit formulas. Originality/value: Particularly, formulas clearly point that the heat transfer rate is not only dependent on the thermal conductivity of the material but it also highly relies on the heat capacitance as well as the density of the nanofluid under consideration.